Impaired renal Na(+) retention in the sgk1-knockout mouse - Wulff, Peer (American Society for Clinical Investigation, 2002)
The serum- and glucocorticoid-regulated kinase (sgk1) is induced by mineralocorticoids and, in turn, upregulates heterologously expressed renal epithelial Na(+) channel (ENaC) activity in Xenopus oocytes. Accordingly, Sgk1 is considered to mediate the mineralocorticoid stimulation of renal ENaC activity and antinatriuresis. Here we show that at standard NaCl intake, renal water and electrolyte excretion is indistinguishable in sgk1-knockout (sgk1(–/–)) mice and wild-type (sgk1(+/+)) mice. In contrast, dietary NaCl restriction reveals an impaired ability of sgk1(–/–) mice to adequately decrease Na(+) excretion despite increases in plasma aldosterone levels and proximal-tubular Na(+) and fluid reabsorption, as well as decreases in blood pressure and glomerular filtration rate.